2020
DOI: 10.3390/ijms21217845
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Nematode-Derived Antigens Alter Colorectal Cancer Cell Proliferation and Migration through Regulation of Cell Cycle and Epithelial-Mesenchymal Transition Proteins

Abstract: As the global incidences of colorectal cancer rises, there is a growing importance in understanding the interaction between external factors, such as common infections, on the initiation and progression of this disease. While certain helminth infections have been shown to alter the severity and risk of developing colitis-associated colorectal cancer, whether these parasites can directly affect colorectal cancer progression is unknown. Here, we made use of murine and human colorectal cancer cell lines to demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Moreover, recent evidence from in vitro experiments using antigens derived from H. polygyrus significantly decreased murine and human CRC-derived cell lines proliferation, which was associated with increased expression of p53 and p21 [91]. In line with this, our research group was the pioneer in demonstrating that excreted-secreted products of T. crassiceps (TcES), instead of a whole infection, reduced in vivo colon tumorigenesis as a therapy delivered at the early stages of CAC (Figure 4b).…”
Section: Excreted-secreted Products Of Helminthsmentioning
confidence: 98%
“…Moreover, recent evidence from in vitro experiments using antigens derived from H. polygyrus significantly decreased murine and human CRC-derived cell lines proliferation, which was associated with increased expression of p53 and p21 [91]. In line with this, our research group was the pioneer in demonstrating that excreted-secreted products of T. crassiceps (TcES), instead of a whole infection, reduced in vivo colon tumorigenesis as a therapy delivered at the early stages of CAC (Figure 4b).…”
Section: Excreted-secreted Products Of Helminthsmentioning
confidence: 98%
“…An increase in the frequency of hepatic cancer was observed in S. japonicum-infected mice exposed to the carcinogen 2-acetylaminofluorene [56] . Other experimental results showed that mice infected with S. japonicum had decreased ability of metabolizing mutagens [58,59] , reduced aflatoxin B1-binding and increased retention of mutagens [60] . In contrast to the categorization of S. haematobium as definitely carcinogenic to humans (group 1), IARC decided that the carcinogenic evidence of S. japonicum infection in humans is limited (group 2B) [5,32,61] .…”
Section: Schistosoma Sppmentioning
confidence: 98%
“…In a separate study, H. polygyrus antigen reduced murine and human colorectal cancer cell (CRC) proliferation, which was associated with the increased expression of p53 and p21. Furthermore, those products increased murine CRC cell migration [ 126 ]. Although the direct influence of Hp-TGM on metastasis has not been demonstrated so far, it cannot be ruled out that this molecule is responsible for at least part of the observed effect of H. polygyrus .…”
Section: Potential Influence Of Nematode Infection On Tumour Developmentmentioning
confidence: 99%